A Implementation Of Fulfillment Of Personal Hygiene Needs In Elderly Dementia In Social Institutions Tresna Werdha Budhi Mulia 01 Cipayung East Jakarta - Fahri, Ahmad; Nasution, Revie Fitria; Iriani, Restu (Fakultas Ilmu Kesehatan, 2025)
Elderly or elderly is a term commonly used for someone who is starting to enter the final stage of development. According to the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 5 of 2018, elderly is when they are over 60 years old (Ministry of Health of the Republic of Indonesia, 2016). General Objectives Able to carry out direct and comprehensive gerontic implementation covering biopsychosocial aspects with a nursing process approach to patients with dementia at the Budhi Mulia 01 Cipayung East Jakarta Social Welfare Home. This case study uses a descriptive case study design. A descriptive case study is an attempt to systematically and accurately describe a situation or a certain population area that is factual. In this case study, the author will systematically describe the nursing care of puzzle therapy for elderly with dementia and the fulfillment of personal hygiene needs for the elderly at the Tresna Werdha Budhi Mulia 01 Social Home in Cipayung, East Jakarta. The research subjects in this case study were 30 elderly people with dementia who provided personal hygiene needs and lived at the Budhi Mulia 01 Cipayung Social Home for the Elderly, East Jakarta. The assessment was conducted on Monday, July 25, 2024 at 08.00 WIB at Wisma Kenanga Panti Tresna Werdha Budhi Mulia 01 Cipayung East Jakarta (PSTW) data was obtained by interviewing patients, friends of patients in the same guesthouse, PSTW clinic nurses, and from medical records. The results of the assessment were obtained Mrs. R, 85 years old, female, Muslim, widow status, last education elementary school, from RT 005 / RW 010 Kalisari, Pasar Rebo District, East Jakarta. The person in charge of Mrs. R who lives at RT 004 / RW 010 Kalisari, Pasar Rebo District, East Jakarta, who is the biological child of the patient. Conclusion: The implementation of nursing care that has been carried out has been effective and has been carried out according to the established plan, namely puzzle therapy. This can be said to be effective because puzzles can train concentration and according to the expectations of the outcome criteria in the theory decreased while the self-care deficit according to expectations also increased. This is due to the cooperation between nurses and patients.